2017
DOI: 10.1111/acer.13367
|View full text |Cite
|
Sign up to set email alerts
|

Using Factor Mixture Models to Evaluate the Type A/B Classification of Alcohol Use Disorders in a Heterogeneous Treatment Sample

Abstract: Background The type A/B classification model for alcohol use disorders (AUDs) has received considerable empirical support. However, few studies examine the underlying latent structure of this subtyping model, which has been challenged as a dichotomization of a single drinking severity dimension. Type B, relative to type A, alcoholics represent those with early age of onset, greater familial risk, and worse outcomes from alcohol use. Method We examined the latent structure of the type A/B model using categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 65 publications
4
12
1
2
Order By: Relevance
“…Participants in the moderate and high severity symptomatic subgroups presented significantly higher rates of baseline harmful alcohol consumption. These findings are consistent with previous empirical research which have demonstrated that some subgroups of AUD with increased severity of alcohol misuse are also characterized with more serious internalizing and externalizing symptoms ( Hildebrandt et al, 2017 , Moss et al, 2010 ). Additionally, multivariate analyses identified the substantial role of baseline coping and conformity motives in the cases of the more severely affected classes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Participants in the moderate and high severity symptomatic subgroups presented significantly higher rates of baseline harmful alcohol consumption. These findings are consistent with previous empirical research which have demonstrated that some subgroups of AUD with increased severity of alcohol misuse are also characterized with more serious internalizing and externalizing symptoms ( Hildebrandt et al, 2017 , Moss et al, 2010 ). Additionally, multivariate analyses identified the substantial role of baseline coping and conformity motives in the cases of the more severely affected classes.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the coping motives, it was assumed that that alcohol consumption serves as a form of emotion regulation among patients with a higher severity symptomatic level, which helps individuals mitigate and cope with unpleasant feelings and emotions ( Berking et al, 2011 ). Previous studies have also demonstrated that subtypes of AUD with elevated internalizing symptomatology show increased rates of drinking in order to relief or self-medicate psychological distress ( Hildebrandt et al, 2017 , Müller et al, 2019 ). In the case of conformity motives, it was hypothesized that the “high severity” symptomatic class might show tendencies also to use alcohol as a means for reducing symptoms related to social anxiety ( Villarosa, Madson, Zeigler-Hill, Noble, & Mohn, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the severity-based latent class solution, the alcohol dependence related items [4][5][6][7] and negative consequences related items [8][9][10] were not separated, but were associated with each other. between Class 2 and Class 3) similar rates of alcohol consumption were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various multiclass models have also been assumed [5]. Current taxonomies consistently posit four alcohol drinking subgroups: low-severity, chronic severe, negative affect, and antisocial subtype [6][7][8]. Additionally, these models highlight the role of comorbid externalizing and internalizing psychopathological symptoms among AUD individuals.…”
Section: Introductionmentioning
confidence: 99%